Impact of Social Media Advertisements on Customer Purchase Intentions - Radha Thangarajan (Journal of Informatics Education and Research, 2025)
These changes have molded the way consumers interact with brands within recent years through which advertising and traditional means and marketing channels of social media like Facebook, Instagram, and Twitter convey. This research explores how the purchase intentions affected by social media ad vary with those elements such as interactivity, credibility, informativeness, and entertainment that mold consumer behavior. In social media, the condition is different from other ways of marketing. Social media is interactive, with two-way communications-the consumers actively interact with the brands through comments and shares, and through feedback, which constitutes electronic word-of-mouth (e-WOM), a tool that informs and persuades possible buyers through recommendations and reviews from their peers. A majority of an extensive literature review enables the synthesis of findings from studies that have indicated that there is increasing strength in social media ads to improve consumer behavior. This is rooted in two prominent research issues- millennial and Gen Z consumers, as these most active users on social media demonstrate higher sensitivity to digital ads. Therefore, the importance of critical engagement strategies, such as personalized targeting and culturally appropriate content, is highlighted in boosting participation and building loyalty with the brand. With this insight, companies can provide more meaningful advertising in order to enhance relations with consumers and will still result in higher conversion rates. Such a study will also add to the field as it puts forward a framework for using social media advertising to enhance brand awareness, engagement, and sustained growth within an increasingly digital world.